Studi Kasus Implementasi E-Book Interaktif sebagai Media Pembelajaran Literasi Membaca di Sekolah Dasar - Suruambo, Juharmin (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This study investigates the implementation of interactive e-books as a medium for reading literacy learning in elementary schools. Reading literacy is a crucial foundation for students' academic success, but many elementary schools face challenges in effectively facilitating the development of these skills in the digital age. Interactive e-books offer the potential to overcome the limitations of traditional learning media by providing a more dynamic and engaging learning experience. This study uses a case study approach focusing on an elementary school in Baubau City. Data were collected through classroom observations, in-depth interviews with teachers and students, and analysis of documents related to reading literacy learning. The results show that the implementation of interactive e-books positively impacts increasing student motivation to learn, active engagement in reading, and text comprehension. Interactive features such as animations, audio, and integrated quizzes proved to be effective in facilitating the understanding of complex literacy concepts. However, several challenges, such as limited access to devices, teacher readiness in integrating technology, and the need for e-book content relevant to the curriculum, need to be addressed. These findings underscore the importance of developing and utilizing interactive e-books as an innovative medium to support reading literacy learning in elementary schools. They also provide recommendations for stakeholders to optimize their use.